Does Intra-African Migration Matter For Intra-African Trade? - OLUBIYI, Ebenezer; POSU, Sunday; OGUNNUSI, Timilehin (EuroEconomica, 2023)
The effect of migration on trade is one of the topical issues in the world and particularly in Africa. The highly populated African countries are expected to aid trade both from demand and supply sides. However, while in intra-African migration is large compared to other continents, the same cannot be said of intra-African trade. Does this mean migration substitutes trade in Africa? Yet there are regional community blocs (RECs) that have engaged in various trade relations in a bid to encouraging trade among members. What implication will migration has on this trade arrangement? This study seeks to find answers to these questions by estimating a panel negative binomial regression of the effect of intra-African migration in intra-African trade with special focus on the RECs. A 6-period data covering 1980, 1990, 2000, 2010, 2013 and 2017 was utilized in the context of modified gravity model. The result confirms the substitutability of trade for migration in Africa. However in ECOWAS and EAC, migration enhances trade. Migration also facilitates exports in COMESA but inhibits imports. No significant effect is observed in the case of ECCAS even though a potential inhibiting effect is observed. The result also establishes trade creation among ECOWAS and ECCAS while trade diversion was observed in EAC and COMESA. Economic implication and recommendations are offered based on these results.